Twisted twenty-six - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2019)
Grandma Mazur has decided to get married again - this time to a local gangster named Jimmy Rosolli. If Stephanie has her doubts about this marriage, she doesn't have to worry for long, because the groom drops dead of a heart attack 45 minutes after saying, "I do." A sad day for Grandma Mazur turns into something far more dangerous when Jimmy's former "business partners" are convinced that his new widow is keeping the keys to a financial windfall all to herself. But the one thing these wise guys didn't count on was the widow's bounty hunter granddaughter, who'll do anything to save her.